No evidence of word-level uncertainty in younger and older adults in self-paced reading. Issue 6 (June 2022) - Cutter, Michael G; Paterson, Kevin B; Filik, Ruth
In a self-paced reading study, we investigated whether older adults maintain a greater level of uncertainty about the identity of words in a sentence than younger adults, potentially due to deficits in visuo-perceptual processing of high-spatial frequencies associated with normal aging. In the experiment, 60 older adults and 60 younger adults read sentences in which an early preposition was either perceptually confusable with another word ( at ; confusable with as ) or not ( toward ), and in which the reading of a subsequent ambiguous verb (e.g., tossed ) should be affected by the confusability of the preposition, while the reading of an unambiguous verb (e.g., thrown ) should not be. This design replicated that of an earlier study conducted by Levy et al. (2009) that found evidence in favour of participants maintaining uncertainty about the confusable preposition in go-past times during natural reading. However, in our study, there was no evidence that either younger or older adults maintained uncertainty about the identity of the perceptually confusable preposition, such that there was no interaction between the preposition's form and subsequent verb ambiguity in self-paced reading times, although we did observe a main effect of verb ambiguity. This represents a failure to replicate the effect observed by Levy et al. when using a different experimental paradigm, and we consider potential causes of our findings at both a methodological and theoretical level.